2017
DOI: 10.1038/s41593-017-0003-2
|View full text |Cite
|
Sign up to set email alerts
|

Mixed selectivity morphs population codes in prefrontal cortex

Abstract: The prefrontal cortex maintains working memory information in the presence of distracting stimuli. It has long been thought that sustained activity in individual neurons or groups of neurons was responsible for maintaining information in the form of a persistent, stable code. Here we show that, upon the presentation of a distractor, information in the lateral prefrontal cortex was reorganized into a different pattern of activity to create a morphed stable code without losing information. In contrast, the code … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
199
4

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(227 citation statements)
references
References 38 publications
24
199
4
Order By: Relevance
“…Fine‐tuning of the target template in relation to distractor features may take place in the lateral prefrontal cortex due to the abundance of neurons with mixed selectivity in this area. A recent study demonstrated that information in working memory in monkey's lateral prefrontal cortex reorganized into a different pattern of activity upon distractor presentation, whereas the same code remained stable in frontal eye fields (FEFs) …”
Section: Indirect Preparatory Distractor Suppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fine‐tuning of the target template in relation to distractor features may take place in the lateral prefrontal cortex due to the abundance of neurons with mixed selectivity in this area. A recent study demonstrated that information in working memory in monkey's lateral prefrontal cortex reorganized into a different pattern of activity upon distractor presentation, whereas the same code remained stable in frontal eye fields (FEFs) …”
Section: Indirect Preparatory Distractor Suppressionmentioning
confidence: 99%
“…A recent study demonstrated that information in working memory in monkey's lateral prefrontal cortex reorganized into a different pattern of activity upon distractor presentation, whereas the same code remained stable in frontal eye fields (FEFs). 63 A challenge for future work will be to establish how such code morphing or template-to-distractor distinctiveness 17 may help, albeit indirectly, the suppression of distractor processing, especially when targets and distractors are highly similar at the feature level. In particular, it is still unclear whether only the target representation is adjusted, or whether the representation of both targets and distractors can be adapted.…”
Section: Indirect Distractor Suppression Through Template-to-distractmentioning
confidence: 99%
“…The macaque was trained to perform a delayed saccade task [7]. Electrode arrays of 16-and 32-channels (256 in total), were implanted in the monkey's brain (see fig.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, building on these previous works, we seek to study the emergence of spatio-temporal coexisting patterns of synchronized and desynchronized behavior, termed chimeralike states, in neurophysiological signals from a macaque monkey and particularly, from prefrontal-cortex intracranial recordings [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation